(untitled) (Journal of Human Sciences, 2018)
Using an econometric model, we investigated FDI inflows to the Libyan market and its determining factors, gross domestic product in real terms GDP, the exchange rate of the Libyan Dinar ER, Inflation INF and the rate of investment RINV from 1970 to 2010, and future of FDI after the Arab spring in Libya and the expected implication on political and economic changes, as the country tends to start a new era to modernize the economy through an ambitious economic reform program.Since the lifting of the UN sanctions in 1999, Libya is at a turning point, both politically as well as economically. Numerous impediments of the economic cooperation removed; hence, there is a scope for a growing developmental dynamics. The Law No 5 of 1997 and its amendments offered tax concessions to investors for the first five years; an exemption on customs duty on imports of materials used in the project; provisions to allow foreigners to buy real estate for their project. FDI inward flows into Libya stood at the lowest level compared with neighboring countries such as Egypt and Tunisia, after maintaining a negative value for the past several years. An empirical model using some macro-economic variables utilized to obtain a general characterization of FDI in the Libyan economy.